2016
DOI: 10.1186/s13045-015-0230-5
|View full text |Cite
|
Sign up to set email alerts
|

Combined deletion of Xrcc4 and Trp53 in mouse germinal center B cells leads to novel B cell lymphomas with clonal heterogeneity

Abstract: BackgroundActivated B lymphocytes harbor programmed DNA double-strand breaks (DSBs) initiated by activation-induced deaminase (AID) and repaired by non-homologous end-joining (NHEJ). While it has been proposed that these DSBs during secondary antibody gene diversification are the primary source of chromosomal translocations in germinal center (GC)-derived B cell lymphomas, this point has not been directly addressed due to the lack of proper mouse models.MethodsIn the current study, we establish a unique mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…Overcome immunotherapy resistance in B-cell lymphoma REVIEW classical Hodgkin lymphoma (HL) present the loss of MHC class I expression (Challa-Malladi et al, 2011;de Charette and Houot, 2018), and diminished MHC class II expression also frequently occurs not only in DLBCL but also in other types of mature B-cell lymphomas (Rimsza et al, 2004;Roberts et al, 2006;Diepstra et al, 2007a;Fangazio et al, 2014;de Charette et al, 2016;Nijland et al, 2017). We recently established a unique mouse model by lineagespecific deletion of a DNA repair gene, Xrcc4, and Trp53 in GC B cells (Chen et al, 2016). This mouse strain spontaneously develops mature B-cell lymphomas, termed G1XP lymphomas (Chen et al, 2016).…”
Section: Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Overcome immunotherapy resistance in B-cell lymphoma REVIEW classical Hodgkin lymphoma (HL) present the loss of MHC class I expression (Challa-Malladi et al, 2011;de Charette and Houot, 2018), and diminished MHC class II expression also frequently occurs not only in DLBCL but also in other types of mature B-cell lymphomas (Rimsza et al, 2004;Roberts et al, 2006;Diepstra et al, 2007a;Fangazio et al, 2014;de Charette et al, 2016;Nijland et al, 2017). We recently established a unique mouse model by lineagespecific deletion of a DNA repair gene, Xrcc4, and Trp53 in GC B cells (Chen et al, 2016). This mouse strain spontaneously develops mature B-cell lymphomas, termed G1XP lymphomas (Chen et al, 2016).…”
Section: Cellmentioning
confidence: 99%
“…We recently established a unique mouse model by lineagespecific deletion of a DNA repair gene, Xrcc4, and Trp53 in GC B cells (Chen et al, 2016). This mouse strain spontaneously develops mature B-cell lymphomas, termed G1XP lymphomas (Chen et al, 2016). G1XP lymphomas resemble the key features of human B-cell lymphomas including reciprocal chromosomal translocations and elevated expression of c-myc (Chen et al, 2016) and downregulation of MHC class I and class II expression (Wang et al, 2019).…”
Section: Cellmentioning
confidence: 99%
“…G1XP lymphomas were generated, established, and cultured as described previously (8). A20 lymphoma cells were obtained from cell line vendor ATCC in 2017.…”
Section: Cell Culturementioning
confidence: 99%
“…There are no good experimental models to study PD1 blockade resistance observed in human Bcell lymphomas. To address these issues, we employed a mouse mature B-cell lymphoma model, G1XP (8), which resembles human B-cell lymphomas, to test therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation